Purchase order for supply, installation and testing of the IT floor trunk, conduit, and groove cutting in the recessed area in different floor of BracU new campus building - Brac University (Brac University, 2023)
This purchase order has been made between Brac University and Everest Trade International for IT floor trunk, conduit and groove cutting for Brac University new campus project.